Biologically active substances of salix purpurea F. Gracilis (Gren. & Godr.) C.K. Schneid. (Salicaceae) - Borodina, Natalia; Kovalyov, Volodimir; Koshovyi, Oleh (ScienceRise: Pharmaceutical Science, 2019)
The medicinal raw materials of many representatives of the Salicaceae family have long been widely used both in folk medicine and in modern pharmaceuticals. Currently, some species of willow are official medicinal raw materials in some European countries. In 2014, "Salicis cortex" acquired the status of official medicinal raw material and included in the State Pharmacopoeia of Ukraine. In this regard, the study of biologically active compounds of different species, varieties and hybrid forms of willow is important, which will allow to expand the range of medicinal plant material both at the expense of local and at the expense of introduced species of willow, common in Ukraine. Aim. Study of qualitative and quantitative composition of biologically active substances of Salix purpurea f. Gracilis (Gren. & Godr.) C.K. Schneid., Growing in Ukraine. Methods of the research. The object of the study were dry shoots of the Salix purpurea f. Gracilis (Gren. & Godr.) C.K. Schneid. Plant raw materials were collected in 2016–2017 years by the NBS named after M. M. Grishko National Academy of Sciences of Ukraine. The component composition of volatile substances was determined using the Agilent Technologies 6890 chromatograph with a mass spectrometer detector 5973. The content of the phenolic substances was determined colorimetrically by the Folin-Ciocalteau method. Component composition of phenolic substances was determined by high performance liquid chromatography (HPLC) using the Prominence LC-20 Liquid Chromatographic System Shimadzu (Japan). Results. The qualitative composition and quantitative content of volatile compounds and phenolic substances of Salix purpurea f. Gracilis (Gren. & Godr.) C.K. Schneid shoots have been determined. It was established that the raw material contains rather high concentrations of volatile compounds, which are dominated by aromatic - in particular, geraniol and eugenol, among the terpenoids, squalene predominates. It was found that phenolic substances are represented by flavonoids and hydroxycinnamic acids. Among substances of phenolic nature dominated by flavanones. The conducted studies confirm the feasibility of further studies of willow species. Conclusions. The qualitative composition and quantitative content of volatile compounds and phenolic substances in Salix purpurea f. Gracilis (Gren. & Godr.) C.K. Schneid shoots have been determined. The studies significantly expanded the data on the chemical composition of raw materials of plants of the genus Salix L. Data obtained from the study of Salix purpurea f. Gracilis (Gren. & Godr.) C.K. Schneid will be used for the planning of pharmacological research and development of QCM for raw materials and medicines